Clozapine toxicity: a cautionary palliative care tale. Issue 3 (13th January 2020) - Macfarlane, Michael; Shahab, Julita; Willis, Derek
Abstract : Objective: This case report presents an unusual case of clozapine toxicity secondary to reduced smoking habit mimicking a patient approaching end of life. Methods: It is a cautionary tale for palliative care specialists, perhaps unaware of the effect of cigarette smoke on metabolism of this antipsychotic, to be aware of. Results: Following specialist advice and change of antipsychotic medication, this patient's condition improved to the point that he was discharged from the hospice. Conclusion: Palliative care specialists should be aware that reducing cigarette consumption can alter metabolism of clozapine, potentially causing drug accumulation and toxicity with features which mimic deterioration towards end of life. Specialist advice should be sought in such a situation.